DIAGNOSIS OF RHEUMATOID ARTHRITIS USING LABORATORY AND INSTRUMENTAL METHODS (World Bulletin of Public Health, 2025)
This article reviews the recent advances in the diagnosis of rheumatoid arthritis (RA) with a focus on immunological methods that enhance diagnostic accuracy and disease activity assessment. The role of various markers, including rheumatoid factor (RF) and anti-citrullinated protein antibodies (ACCP), in disease detection and prognosis is discussed. The importance of laboratory indicators such as C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) for evaluating inflammation and disease activity is also highlighted. Furthermore, the role of imaging methods, such as ultrasound and magnetic resonance imaging (MRI), in early diagnosis and treatment monitoring is examined. The article emphasizes the need for further development of diagnostic methods to ensure timely RA diagnosis and effective treatment monitoring.
Keywords: Rheumatoid arthritis; diagnosis; rheumatoid